Membangun Tv Dakwah Berbasis Streaming Technology - Muhayat Muhayat (UIN Antasari Banjarmasin, 2016)
Da'wah is an activity that is universal, not limitation of space and time, it all depends on the needs and circumstances the object of Da'wah. In the perspective of contemporary, Da'wah through the mass media, especially television is still very relevant because television as an audio-visual medium, is able to capture 94% channel entry message-either message or information come to our brain through both eyes and ears. Once displayed agenda in television, normal people could remember 50% from what they see and hear. In other words, people will remember 85% from what they see and hear from television after 3 hours and 65% for the next 3 days. But to build a conventional TV are very expensive, it is necessary creativity to realize Da'wah TV reliable yet inexpensive. To achieve this, the most powerful candidate is build Da'wah TV based on streaming technology, a technology that allows broadcast TV in real-time as well as On Demand through the Internet. This paper will describe the analysis and design Da'wa TV based on streaming technology with systems development methodology Luther Version consisting of six phases; concept, design, material collecting, assembly, testing and distribution.